Analysis of the Potential of Remote Monitoring and Control Systems for Energy Efficiency in Office Buildings - Roy Leo Rensius Hutauruk; Zuraidah Tharo; Pristisal Wibowo (Sean Institute, 2025)
Energy consumption in office buildings represents a significant portion of operational costs and environmental impact. Efficient energy management has therefore become a critical priority. This study analyzes the potential of implementing remote monitoring and control systems to improve energy efficiency in office buildings. The system integrates Internet of Things (IoT) technologies and microcontroller-based controllers to monitor and regulate electrical loads such as lighting, air conditioning, and other office equipment. Data collection and analysis were conducted through sensor integration, cloud-based dashboards, and control algorithms. The results show that real-time energy monitoring and automated control can reduce unnecessary energy usage by up to 25%, improve responsiveness to occupancy patterns, and enable predictive maintenance. The system also supports remote access via web or mobile interfaces, allowing facility managers to make informed decisions. The findings suggest that remote monitoring and control systems offer significant potential to enhance energy efficiency, reduce operational costs, and contribute to sustainable building management practices.